2021
DOI: 10.1097/md.0000000000022946
|View full text |Cite
|
Sign up to set email alerts
|

The correlation of long non-coding RNA NEAT1 and its targets microRNA (miR)-21, miR-124, and miR-125a with disease risk, severity, and inflammation of allergic rhinitis

Abstract: The present study aimed to investigate the correlation of long non-coding RNA nuclear-enriched abundant transcript 1 (lncRNA NEAT1) with microRNA (miR)-21, miR-124, and miR-125a, and their associations with disease risk, severity, and inflammatory cytokines of allergic rhinitis (AR). Totally 70 AR patients and 70 non-atopic obstructive snoring patients (as controls) were recruited. Inferior turbinate mucosa samples were collected from all participants for lncRNA NEAT1, its targets (miR-21, miR-124, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 25 publications
0
23
0
Order By: Relevance
“…In our study, we found that lnc-NEAT1 was elevated, while miR-21 Furthermore, we also found that lnc-NEAT1 was negatively correlated with miR-21 and miR-125a, which might be explained by that lnc-NEAT1 could target miR-21 and miR-125a in immunological disease (such as allergic rhinitis), the similar targeting manner might also exist in RA. 7 A previous study has illustrated that lnc-NEAT1 is positively correlated with disease activity in SLE patients 21 ; furthermore, another study shows that miR-125a negatively correlates with disease severity in patients with Crohn's disease. 22 However, the correlation of lnc-NEAT1 with miR-21 and miR-125a, as well as their correlation with clinical characteristics in RA, is rarely reported.…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations
“…In our study, we found that lnc-NEAT1 was elevated, while miR-21 Furthermore, we also found that lnc-NEAT1 was negatively correlated with miR-21 and miR-125a, which might be explained by that lnc-NEAT1 could target miR-21 and miR-125a in immunological disease (such as allergic rhinitis), the similar targeting manner might also exist in RA. 7 A previous study has illustrated that lnc-NEAT1 is positively correlated with disease activity in SLE patients 21 ; furthermore, another study shows that miR-125a negatively correlates with disease severity in patients with Crohn's disease. 22 However, the correlation of lnc-NEAT1 with miR-21 and miR-125a, as well as their correlation with clinical characteristics in RA, is rarely reported.…”
Section: Discussionmentioning
confidence: 95%
“…Furthermore, we also found that lnc‐NEAT1 was negatively correlated with miR‐21 and miR‐125a, which might be explained by that lnc‐NEAT1 could target miR‐21 and miR‐125a in immunological disease (such as allergic rhinitis), the similar targeting manner might also exist in RA. 7 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, it is possible that miR-21 and miR-140 upregulate Th1 differentiation but downregulate Th2 differentiation by targeting GATA-3 and Tbet. 17,22,23 This would explain the positive correlation of miR-21 and miR-140 expression with Th1 cytokine expression as well as the negative correlation of miR-21 and miR-140 expression with Th2 cytokine expression.…”
Section: Correlation Of Mir-140 Expression With Disease Features and Characteristics In Ar Patientsmentioning
confidence: 99%